Invasive property of an attenuated gdha- derivative of pasteurella multocida B:2 - Muhammad Azam, Farahani (2015)
Haemorrhagic septicaemia (HS) is a disease of buffaloes and cattle that can cause acute and fatal mortality if contracted. The animals are infected by the bacteria through the intranasal pathway which translocated intracelullarly into the vascular system. Live-attenuated vaccine, containing attenuated live bacteria is the alternative vaccine that has been shown to confer longer period of immunity towards the field-animals. The attenuated GdhA- derivative of Pasteurella multocida B:2 has been proven to be a suitable candidate as a live-attenuated vaccine towards HS among other live-attenuated strains tested. A further insight into the intracellular viability and pathogenicity of this disease can be discovered by understanding the mechanism of interaction between the host cell and the vaccine candidate. In this study, the GdhA- derivative strain was shown to adhere and to invade bovine aortic endothelial cells (BAECs) in vitro alongside another derivative strain, the AroA- derivative and the wild-type of P. multocida B:2 strains as a control. Infection of GdhA- derivative towards BAECs had shown no cytotoxicity effect with >80% viability towards the cell lines through trypan blue viability assessment. Adhesion and invasion of the GdhA- derivative was shown to be more efficient with highest adhesion rate (45.75 ± 5.74 number of bacteria/BAEC cell) and invasion rate (1.41 ± 0.27 number of bacteria/BAEC cell) when compared to the AroA- derivative and the wild-type strains.